Quotas and Gender Gaps in Political Participation among Established Industrial European Democracies: Distinguishing Within- and Across-Country Effects. (September 2017) - Beauregard, Katrine
This paper proposes to investigate the influence of legislative quotas on gender differences in political participation by analyzing the within- and across-country effects of quotas. Gender quotas can signal to women that their presence in politics is welcome, leading to a subsequent increase in their involvement in political activities. This change in political behavior should not be reproduced in men; thus, when gender quotas are present, the gap between men's and women's participation narrows. Using the European Values Survey and data from eighteen European democracies, this paper demonstrates that this indeed occurs for some political activities when gender gaps are compared before and after the introduction of quotas within countries. This result, however, is not replicated for across-country analyses. European countries without legislative gender quotas tend to have smaller gender gaps than countries with them. This result is explained by referring to the context of the adoption of gender quotas.